Age‐dependent electrocardiographic changes in Pgc‐1β deficient murine hearts. (29th November 2017) - Ahmad, Shiraz; Valli, Haseeb; Salvage, Samantha C; Grace, Andrew A; Jeevaratnam, Kamalan; Huang, Christopher L‐H
Summary: Increasing evidence implicates chronic energetic dysfunction in human cardiac arrhythmias. Mitochondrial impairment through Pgc‐1 β knockout is known to produce a murine arrhythmic phenotype. However, the cumulative effect of this with advancing age and its electrocardiographic basis have not been previously studied. Young (12‐16 weeks) and aged (>52 weeks), wild type (WT) (n = 5 and 8) and Pgc‐1 β −/− (n = 9 and 6), mice were anaesthetised and used for electrocardiographic (ECG) recordings. Time intervals separating successive ECG deflections were analysed for differences between groups before and after β1‐adrenergic (intraperitoneal dobutamine 3 mg/kg) challenge. Heart rates before dobutamine challenge were indistinguishable between groups. The Pgc‐1 β −/− genotype however displayed compromised nodal function in response to adrenergic challenge. This manifested as an impaired heart rate response suggesting a functional defect at the level of the sino‐atrial node, and a negative dromotropic response suggesting an atrioventricular conduction defect. Incidences of the latter were most pronounced in the aged Pgc‐1 β −/− mice. Moreover, Pgc‐1 β −/− mice displayed electrocardiographic features consistent with the existence of a pro‐arrhythmic substrate. Firstly, ventricular activation was prolonged in these mice consistent with slowed action potential conduction and is reported here for the first time. Additionally, Pgc‐1 β −/− mice had shorter repolarisation intervals. These were likely attributable to altered K + conductance properties, ultimately resulting in a shortened QTc interval, which is also known to be associated with increased arrhythmic risk. ECG analysis thus yielded electrophysiological findings bearing on potential arrhythmogenicity in intact Pgc‐1 β −/− systems in widespread cardiac regions.